Epistemic injustice in the age of evidence-based practice: The case of fibromyalgia - Kristin Margrethe Heggen; Henrik Berg (Humanities & Social Sciences Communications, 2021)
Abstract The aim of this paper is to analyze epistemic interactions in healthcare practices. In clinical encounters, participants exchange and interpret knowledge. Patients suffering from fibromyalgia often report that healthcare professionals do not take their testimonies and interpretations seriously. Such experiences will be explored using the concept of epistemic injustice. Epistemic injustice is wrong done to someone in their capacity as a knower. In healthcare settings, epistemic injustice occurs when patients experience an unjustified discrediting as unreliable informants of their own illness experiences. First, we will argue that patients’ epistemic marginalization can be reframed as an epistemological problem. There is a gap between patients’ lived experience of illness and professionals’ conceptualization of illness as disease. This gap leads to two distinct conceptualizations, possibly causing harm to patients’ capacity as first-hand knowers. Second, we will analyze epistemic injustice in light of the dominant model of knowledge translation in medicine and healthcare, namely evidence-based practice (EBP). EBP intends to diminish the gap between scientific knowledge and clinical practice. EBP prioritizes knowledge obtained through clinical research over other forms of clinical knowledge and has the potential for harmful epistemic devaluation of patients’ stories.